Kant's system of nature and freedom selected essays - Guyer, Paul, 1948- (Oxford : Clarendon, 2010)
The governing theme of the volume is the role of systematicity in Kant's theoretical and practical philosophy. Featuring two new papers and and introduction to orient the reader, this text will be useful to anyone working on the history of philosophy and related areas of ethics, philosophy of science, and metaphysics.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Kant, Immanuel, -- 1724-1804.; Natural history -- Philosophy; Ethics